PEMANFAATAN TEKNIK PENGINDERAAN JAUH UNTUK PEMETAAN TINGKAT KERAWANAN KEBAKARAN PERMUKIMAN (Geo-Image, 2013)
Settlement and fire constitute complex problems facing large urban cities such as Semarang. The article attempts to examine how and to what extent the utilization of remote sensing techniques for mapping the vulnerability of fire in the city of Semarang. Where are the areas in Semarang who have a high vulnerability? Based on this research, it can be concluded among other things, (1) Quickbird satellite image year 2006 can be used to extract physical parameters fire vulnerability with an average accuracy of 85.8% (2) the level of vulnerability to fires in the study area was divided into 3 classes the details: the potential of low fire Southern District of Semarang 17.327 ha (1.02%), Middle District of Semarang 18.768 ha (1.11%), and the Eastern District of Semarang 9.712 Ha (0.57%). Are potential fire, District of South Semarang 207.946 ha (12.27%), Middle District of Semarang 217.855 ha (12.85%) and the Eastern District of Semarang 186.625 ha (11.10%). High fire potential Southern District of Semarang 109.66 Ha (6.47%), Middle District of Semarang 98.68 Ha (5.82%) and the Eastern District of Semarang 117.591 ha (6.94%). Residential area that is prone to fire hazard is characterized by a solid physical condition of buildings, the layout is irregular, and low quality of construction, coupled with the lack of fire fighting facilities